Material de propagacion y siembra de yuca - Celis, E. (International Center for Tropical Agriculture, 1973)
Cassava can be propagated by true seeds and vegetative material. Obtaining true seeds is difficult and resulting plants have longer life cycles, rendering lower tuber production. Thus cuttings are preferred. Recommendations on the optimal length of cuttings vary greatly. Factors involved in using cuttings are plant age, planting sanitation, length of cuttings, planting distance, cutting viability and orientation of cuttings when planted. (CIAT)